Pengaruh Konflik dan Ambiguitas Peran Terhadap Kepuasan Kerja Dimediasi oleh Kelelahan Emosional - Bulan, Tapi Rondang Ni (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2022)
Employee job satisfaction can be achieved if various employee expectations can be fulfilled by carrying out their work. This study aims to analyze the effect of conflict and role ambiguity on job satisfaction with emotional exhaustion as a mediating variable. This research was conducted at the Sistem Administrasi Manunggal Satu Atap (SAMSAT) in South Medan. The research respondents were all 72 employees. This type of research is causality. The results of the study prove that partially or simultaneously conflict and role ambiguity have a significant effect on job satisfaction either directly or through emotional exhaustion as a mediating variable. The higher the conflict and ambiguity of the roles that employees live, it will trigger the emergence of emotional exhaustion and will ultimately reduce job satisfaction, and vice versa. Therefore, the leadership needs to conduct a proper job analysis in order to identify the suitability of employee characteristics required for each position in the agency. Briefings to explain various forms of work plans also need to be carried out periodically to provide a better understanding of the tasks that must be accomplished by each employee.